The combination of CHK1 inhibitor with G-CSF overrides cytarabine resistance in human acute myeloid leukemia. Issue 1 (December 2017) - Di Tullio, Alessandro; Rouault-Pierre, Kevin; Abarrategi, Ander; Mian, Syed; Grey, William; Gribben, John; Stewart, Aengus; Blackwood, Elizabeth; Bonnet, Dominique
Abstract Cytarabine (AraC) represents the most effective single agent treatment for AML. Nevertheless, overriding AraC resistance in AML remains an unmet medical need. Here we show that the CHK1 inhibitor (CHK1i) GDC-0575 enhances AraC-mediated killing of AML cells both in vitro and in vivo, thus abrogating any potential chemoresistance mechanisms involving DNA repair. Importantly, this combination of drugs does not affect normal long-term hematopoietic stem/progenitors. Moreover, the addition of CHK1i to AraC does not generate de novo mutations and in patients' samples where AraC is mutagenic, addition of CHK1i appears to eliminate the generation of mutant clones. Finally, we observe that persistent residual leukemic cells are quiescent and can become responsive to the treatment when forced into cycle via granulocyte colony-stimulating factor (G-CSF) administration. This drug combination (AraC+CHK1i+G-CSF) will open the doors for a more efficient treatment of AML in the clinic. Overriding cytarabine resistance in AML remains an unmet medical need. Here, the authors show that the CHK1 inhibitor GDC-0575 in combination with cytarabine and G-CSF has a significant anti-leukemic effect without toxicity to normal marrow stem and progenitor cells.